2010
DOI: 10.1096/fj.10-156638
|View full text |Cite
|
Sign up to set email alerts
|

Prolonged mechanical unloading affects cardiomyocyte excitation‐contraction coupling, transverse‐tubule structure, and the cell surface

Abstract: Prolonged mechanical unloading (UN) of the heart is associated with detrimental changes to the structure and function of cardiomyocytes. The mechanisms underlying these changes are unknown. In this study, we report the influence of UN on excitationcontraction coupling, Ca 2؉ -induced Ca 2؉ release (CICR) in particular, and transverse (t)-tubule structure. UN was induced in male Lewis rat hearts by heterotopic abdominal heart transplantation. Left ventricular cardiomyocytes were isolated from the transplanted h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
71
0
1

Year Published

2010
2010
2023
2023

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 71 publications
(76 citation statements)
references
References 52 publications
(92 reference statements)
4
71
0
1
Order By: Relevance
“…79,81 Another study showed normalization of SERCA and SERCA/phospholamban ratios early after LVAD implantation, with reversion back to failing levels with prolonged LVAD support. 82 There is also growing evidence that alterations in T-tubule structures (which are colocalized to areas of impaired Ca 2+ release) are an important cause of deterioration in cardiac myocyte function in a range of cardiac diseases. 82 One study showed irregular distribution of the T-tubules and profound disruption of the openings of the T-tubules and the cell surface in cardiac myocytes after prolonged unloading 82 with a smaller proportion of T-tubule openings in their ordinary position.…”
Section: Duration Of Unloadingmentioning
confidence: 99%
“…79,81 Another study showed normalization of SERCA and SERCA/phospholamban ratios early after LVAD implantation, with reversion back to failing levels with prolonged LVAD support. 82 There is also growing evidence that alterations in T-tubule structures (which are colocalized to areas of impaired Ca 2+ release) are an important cause of deterioration in cardiac myocyte function in a range of cardiac diseases. 82 One study showed irregular distribution of the T-tubules and profound disruption of the openings of the T-tubules and the cell surface in cardiac myocytes after prolonged unloading 82 with a smaller proportion of T-tubule openings in their ordinary position.…”
Section: Duration Of Unloadingmentioning
confidence: 99%
“…Direct evidence for this mechanism was demonstrated by mechanical unloading of the ischaemic failing heart in the rat by heterotopic abdominal heart transplantation; this procedure reversed t-tubule remodelling and normalised local Ca 2+ release (Ibrahim et al 2012). The same procedure used for prolonged mechanical unloading of normal hearts led to loss of t-tubule structure and impaired Ca 2+ signalling (Ibrahim et al 2010), indicating that there is a 'Goldilocks zone' of mechanical load. The synchronisation between myocytes also appears to be important, as dyssynchronous heart failure in the dog is characterised by loss of t-tubule structure and impaired calcium release that can be reversed by cardiac resynchronisation therapy (Sachse et al 2012;Li et al 2015).…”
Section: Mechanisms Of T-tubule Remodellingmentioning
confidence: 99%
“…Cardiac atrophy was induced in syngeneic male Lewis rats (270±5 g, n= 34, Charles River, Sulzfeld, Germany) by heterotopic abdominal heart transplantation as previously described [12,14,21,22,29,40,41,45,46]. The donor heart was harvested under deep anaesthesia (thiopental-sodium, 100 mg/kg body weight) and was transplanted into the abdominal cavity of the recipient rat under isoflurane anaesthesia (2-2.5 %).…”
Section: Animal Modelmentioning
confidence: 99%
“…The transplanted (atrophic) and the orthotopic (control) hearts of the recipient animal were removed in deep anaesthesia (thiopental-sodium, 100 mg/kg body weight) 2 weeks after transplantation. An unloading period of 2 weeks was chosen to induce a stable cardiac atrophy in accordance with previous studies [12,14,40,41] while avoiding the detrimental effects of prolonged unloading on cardiac excitation-contraction coupling and contractility [21,22,29,45]. For all experiments, the orthotopic hearts served as corresponding controls.…”
Section: Animal Modelmentioning
confidence: 99%